Psychosocial Reserve Capacity, Family Background and Selection of an Educational Path – A Longitudinal Study From Finland - Claro, Paulyn Jean A (Archīum Ateneo, 2022)
Finnish students start academic or vocational track in upper secondary education at age 16 years. Track placement is based on grades, but family background and psychosocial resources may have influences. Using 2014 survey data of Grade 9 students in Helsinki Metropolitan area linked to the Joint Application Registry data as of 2017, we fitted two-level, sex-stratified, generalized structural equation models to determine how reserve capacity (academic self-efficacy and social support), family background, and the comprehensive schools predict track placement. Adjusting for the effect of grades, low reserve capacity and disadvantaged family background increased probabilities of vocational track and non-placement of students. Schools also affected track placement, suggesting differences among comprehensive schools in the area. Findings imply that building reserve capacities of adolescents, through enhancing academic self-efficacy and social support, particularly in those with disadvantaged backgrounds, could increase chances of academic track placement in upper secondary school.